The UNITED NATIONS SECURITY COUNCIL'S POWERLESSNESS TO HALT THE RUSSIA-UKRAINE CONFLICT BETWEEN 2022 - 2024 - Aryo Wicaksono; Ratnawati (Jurnal Paradigma, 2025)
This Study is to answer why the United Nations Security Council can not reduce the escalation of Russia-Ukraine conflict from 2022 until 2024. This conflict still exists and the Security Council looks like did not stop or reduce the conflict at least into a ceasefire agreement, while the Security Council has the authority and ability to stop or reduce this conflict. Any research about the United Nations and Security Council role focuses on comparative normative studies based on legal review or law approach. This study offers a new exploration and finds another perspective about the root problem: the United Nations Security Council can not reduce the Russia-Ukraine conflict. With Hegemonic Stability theoretical approach by Robert Gilpin on Pease (2009) and International Organization Role as an Instrument concept by Clive Archer (2001). This Research deeply explores why the UN Security Council can not use its authority to reduce Russia-Ukraine Conflict. Using qualitative methodology based on depth literature review study and explanatory analysis. The finding reveal that the reform of the League of Nations into the United Nations and the decision-making system of the United Nations and Security Council its closely related to the World War II winner's interest to maintain their power to influence by occupying strategic positions as Permanent Member of the Security Council that have privilege to use absolute negative vote (Veto rights). Russia, as the main actor in this conflict, uses the weakness of the UN Security Council’s decision-making system with Russia's strategic positions as a Permanent Member of the UN Security Council.